MIKC-type MADS-box transcription factor gene family in peanut: Genome-wide characterization and expression analysis under abiotic stress - Mou, Yifei; Yuan, Cuiling; Sun, Quanxi; Yan, Caixia; Zhao, Xiaobo; Wang, Juan; Wang, Qi; Shan, Shihua; Li, Chunjuan (Frontiers in Plant Science, 2022)
Peanut (Arachis hypogaea) is one of the most important economic crops around the world, especially since it provides vegetable oil and high-quality protein for humans. Proteins encoded by MADS-box transcription factors are widely involved in regulating plant growth and development as well as responses to abiotic stresses. However, the MIKC-type MADS-box TFs in peanut remains currently unclear. Hence, in this study, 166 MIKC-type MADS-box genes were identified in both cultivated and wild-type peanut genomes, which were divided into 12 subfamilies. We found a variety of development-, hormone-, and stress-related cis-acting elements in the promoter region of peanut MIKC-type MADS-box genes. The chromosomal distribution of peanut MADS-box genes was not random, and gene duplication contributed to the expansion of the MADS-box gene family. The interaction network of the peanut AhMADS proteins was established. Expression pattern analysis showed that AhMADS genes were specifically expressed in tissues and under abiotic stresses. It was further confirmed via the qRT-PCR technique that five selected AhMADS genes could be induced by abiotic and hormone treatments and presented different expressive profiles under various stresses. Taken together, these findings provide valuable information for the exploration of candidate genes in molecular breeding and further study of AhMADS gene functions.